2020
DOI: 10.3389/fmed.2020.00139
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Surgical Margin on the Prognosis of Early Hepatocellular Carcinoma (≤5 cm): A Propensity Score Matching Analysis

Abstract: The influence of surgical margin on the prognosis of patients with early solitary hepatocellular carcinoma (HCC) (≤5 cm) is undetermined.Methods: The data of 904 patients with early solitary HCC who underwent liver resection were collected for recurrence-free survival (RFS) and overall survival (OS). Propensity score matching (PSM) was performed to balance the potential bias.Results: Log-rank tests showed that 2 mm was the best cutoff value to discriminate the prognosis of early HCC. Liver resection with a >2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 43 publications
2
25
0
Order By: Relevance
“…Whether surgical resection should be performed with wide or narrow surgical margin remains controversial in MVI-positive HCC patients. Several studies evaluated the relationship among surgical margin width, surgical outcomes and MVI status using measurement cut-offs for surgical margin width of 0.2, 0.5, and 1 cm ( 9 , 18 , 46 , 47 ). Since the incidence of MVI was correlated with tumor size, and MVI were reported to mainly present in the surgical margin adjacent to tumor, increased surgical margin width may improve surgical outcomes ( 31 ).…”
Section: And Selection Of Surgical Typementioning
confidence: 99%
See 2 more Smart Citations
“…Whether surgical resection should be performed with wide or narrow surgical margin remains controversial in MVI-positive HCC patients. Several studies evaluated the relationship among surgical margin width, surgical outcomes and MVI status using measurement cut-offs for surgical margin width of 0.2, 0.5, and 1 cm ( 9 , 18 , 46 , 47 ). Since the incidence of MVI was correlated with tumor size, and MVI were reported to mainly present in the surgical margin adjacent to tumor, increased surgical margin width may improve surgical outcomes ( 31 ).…”
Section: And Selection Of Surgical Typementioning
confidence: 99%
“…Wang et al. ( 46 ) evaluated the influence of surgical margin on the prognosis of patients with HCC ≤ 5 cm and found that both the RFS and OS rates showed no significant difference in narrow (≤0.2 cm) and wide-margin (>0.2 cm) LR for the patients without MVI. However, for HCC patients with MVI, the narrow-margin LR showed poorer surgical outcomes than the wide-margin LR.…”
Section: And Selection Of Surgical Typementioning
confidence: 99%
See 1 more Smart Citation
“…Dates were not further divided by tumor sizes during the enrollment process, which would also have an impact on the patient's prognosis. Some studies found that different tumor sizes (31,32) and the shortest distance from the edge of the tumor to the plane of surgical margin (33)(34)(35) would significantly affect post-operative outcomes, yet no further discussion was done in the survival analysis in this study. The issues mentioned above need to be analyzed by further multi-center and extensive sample data.…”
Section: Discussionmentioning
confidence: 90%
“…Partial hepatectomy is the first choice for patients with solitary liver cancer ≤ 5 cm and good liver function[ 9 ]. However, if the lesion is not fully resected, the residual MVI near the surgical margin may be an important cause of recurrence in patients with HCC[ 14 ], and some studies have demonstrated that extended resection can reduce the early recurrence rate of patients with liver cancer complicated with MVI[ 15 ]. Therefore, the present study has certain reference value for surgery choice in patients with liver cancer.…”
Section: Discussionmentioning
confidence: 99%